The cooperative venture - Remy Lllerena, Gastón (2021)
The current so-called social economy has a significant importance in many advanced economies, others are Cooperatives. Institutions that add to its own objectives to meet the purposes of social character, other than the simple profit maximization pursuing commercial or commercial companies to use.Within this institutional diversity are cooperatives of different nature which have greater economic weight and especially social for its historical roots. True, they have also suffered the rigors of the crisis, but no more than the rest of the enterprise system; and in any case, responses to the crisis have also prevailed these differentials social objectives, with relatively minor reductions in employment and distribution of adjustment costs less skewed than in conventional companies.The social economy, which is what characterizes cooperatives, emphasizes solidarity than in conventional companies has a different value; perhaps also because much greater extent tune with the trend in the forms of "collaborative economy" emerging from the hand of the spread of information technology and communication. There are cooperative companies with more tradition than many competing companies. Lower wage dispersion and employee participation in decision-making are the features that characterize such enterprises in the social economyIt should grant greater prominence to such institutions. Our authorities would do well to take advantage of the established tradition in our country and care for the successful survival of this sector, not so much protecting them against competition, but stimulating efficiency and avoiding penalties, particularly of a fiscal nature. Capitalism needs of various species, and cooperatives, can improve the performance of all corporate fauna, with greater degrees of identification with the economic system and own generation of prosperity.